The effect of global value chain position on green technology innovation efficiency: From the perspective of environmental regulation - Dianxi Hu (Elsevier, 2021)
Under the open economy, whereas the manufacturing industry has realized transformation and upgrading by the embedding global value chain (GVC) division system, the problems of energy consumption and environmental damage caused by the industry have attracted increasing attention from society. In this paper, the industry classification standard of Trade in Value Added (TiVA) database is used to integrate China’s manufacturing industry during 2006–2015. Based on the indicator measurement, corresponding panel data models are constructed to study the impacts of the GVC position on green technology innovation efficiency (GTIE) in the context of environmental regulation. The empirical results show that: (1) The rise of the GVC embedding position significantly promotes the GTIE, and there is industry heterogeneity characterized by pollution intensity and factor density. (2) There is a positive moderating effect and a double threshold effect of environmental regulation on the relationship between the GVC position and the GTIE. The above research findings offer a certain managerial enlightenment for the manufacturing industry of developing countries to guide adjustment of environmental regulation policies, alleviate the pressure on resources and the environment, and even cultivate a new momentum of sustainable economic growth.